PERAN GURU PAI-BP DALAM INTERNALISASI NILAI-NILAI QUR’ANI SEBAGAI DASAR PEMBENTUKAN KARAKTER SISWA ERA DIGITAL DI SEKOLAH DASAR NEGERI 1 JATILAWANG - Sarah Nur'aeni Khoiriyah; Aisyah Fadhillah; Novi Nur Sa’diyah; M. Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Religious Education and Character Education (PAI-BP) serves as the primary vehicle for internalizing Quranic values, ensuring they are embedded in students' attitudes, speech, and behavior. This internalization occurs not only through classroom learning activities but also through various religious practices that occur throughout school life. This research focuses on the synergy between PAI-BP learning and religious practice activities such as Dhuha prayer and Dzuhur prayer in congregation, short Quranic recitation sessions, Quranic recitation attendance records at each PAI-BP meeting, and guidance and counseling sessions directly involving PAI teachers. This study employed a descriptive qualitative approach, with PAI-BP teachers and students of SD Negeri 1 Jatilawang as subjects. Data were collected through observation, interviews, and documentation. Data were then analyzed through data reduction, data presentation, and conclusions were drawn. The results indicate that PAI-BP learning plays a strategic role in shaping students' Quranic character through two main channels: structured classroom learning and religious practice activities within the school environment. Values ​​such as ṣidq (honesty), amanah (responsibility), istiqamah (discipline), and rahmah (compassion) are internalized through teacher role models, routine worship, and consistent religious guidance utilizing social media and digital applications. Islamic Religious Education (PAI-BP) teachers serve not only as instructors but also as role models and spiritual guides for students. Keywords: internalization, Islamic Religious Education (PAI-BP) teachers, Quranic values, character building.